INCREASED LEVELS OF MIRNA-146A IN SERUM AND HISTOLOGIC SAMPLES OF PATIENTS WITH UVEAL MELANOMA - ANDREA RUSSO; Rosario Caltabiano; Antonio Longo; Teresio Avitabile; Livio Marco Franco; Vincenza Bonfiglio; Lidia Puzzo; Marco Ragusa; Michele Reibaldi (Frontiers Media S.A., 2016)
Purpose: to analyze MiRs expression in serum of UM patients, respect to healthy donors, and to compare this data with MiRs expressed in formalin-fixed, paraffin-embedded UM samples.Methods: Expression profile of 754 miRNAs was performed in serum from patients with uveal melanoma that underwent primary enucleation. The level of miRNAs increased in serum was individually analyzed on FFPE UM samples and compared to choroidal melanocytes from unaffected eyes.Results: 14 patients with uveal melanoma were included in the study. We found 8 serum miRNAs differentially expressed compared to normal controls: 2 upregulated miRNAs (miR-146a, miR-523); 6 downregulated miRNAs (miR-19a, miR-30d, miR-127, miR-451, miR-518f, miR-1274B). When data on upregulated miRNAs were singularly validated only a significant overexpression of miR-146a was found. A statistically significant upregulation of miRNA-146a was also found on FFPE UM samples, compared to choroidal melanocytes from unaffected eyes. Conclusions: miRNA-146a is increased in serum of patients with UM and in FFPE tumour samples. Further studies will show if it could be considered a potential marker of UM in the blood.